Production of fig seedlings in alternative substrates in the Upper-Middle Gurgueia region - Miranda, Assussena Carvalho; Queiroz, Ana Paula Moreira; Soares, Isabel Edite Ferreira; Junior, Francisco Almir Campelo Monte; Aguiar, Cibele Divino; Pereira, Gustavo Alves (Comunicata Scientiae, 2019)
Given the importance of determining which substrate source attends to the need of each fruit species and at the same reducing production costs, this work aimed to evaluate the quality of fig seedlings, cultivar ‘Roxo de Valinhos’, in alternative substrates in the Upper-Middle Gurgueia region, Piauí state. The treatments consisted of Sand (SND), Decomposed Moriche Palm Stem (DMT); Goat+Sheep Manure (GSM), Ravine Soil (TBA), and Commercial Substrate (COM). A Randomized Block Design (RBD) was adopted, with 4 replications and 5 experimental units. The analyzed variables were: Sprouting rate index (SRI), branch length (BRL), branch diameter (BRD), number of leaves in the branch (NLB), chlorophyll A (CLA), chlorophyll B (CLB), shoot fresh matter (SFM), root fresh matter (RFM), shoot dry matter, (SDM) root dry matter (RDM), rooted cuttings (ENR), root length (RL) and volume of the root system (VRS). A significant effect of the substrates was verified for all variables, except chlorophyll A, chlorophyll B, number of branches, and branch diameter. Due to the chemical characteristics of the goat+sheep manure, it provided the necessary conditions for the growth and development of the shoot part and root system, revealing to be superior to the remaining substrates. Therefore, it may be concluded that the goat+sheep manure provides all the essential nutrients for the quality production of fig seedlings, cultivar ‘Roxo de Valinhos’, allowing the rooting of 100% of the cuttings.